Heme Structural Perturbation of PEG-Modified Horseradish Peroxidase C in Aromatic Organic Solvents Probed by Optical Absorption and Resonance Raman Dispersion Spectroscopy - Huang, Qing (Biophysical Society, 2003)
The heme structure perturbation of poly(ethylene glycol)-modified horseradish peroxidase (HRP-PEG) dissolved in benzene and toluene has been probed by resonance Raman dispersion spectroscopy. Analysis of the depolarization ratio dispersion of several Raman bands revealed an increase of rhombic B(1g) distortion with respect to native HRP in water. This finding strongly supports the notion that a solvent molecule has moved into the heme pocket where it stays in close proximity to one of the heme's pyrrole rings. The interactions between the solvent molecule, the heme, and the heme cavity slightly stabilize the hexacoordinate high spin state without eliminating the pentacoordinate quantum mixed spin state that is dominant in the resting enzyme. On the contrary, the model substrate benzohydroxamic acid strongly favors the hexacoordinate quantum mixed spin state and induces a B(2g)-type distortion owing to its position close to one of the heme methine bridges. These results strongly suggest that substrate binding must have an influence on the heme geometry of HRP and that the heme structure of the enzyme-substrate complex (as opposed to the resting state) must be the key to understanding the chemical reactivity of HRP.